Vertebral and Pulmonary Actinomycosis Mimicking Metastatic Lung Cancer - Fichte, Susanne; Brodhun, Michael; Göttinger, Sascha; Rosahl, Steffen; Klisch, Joachim; Gerlach, Rüdiger (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Actinomycosis of the spine with spinal cord compression is rare. Only 22 cases are reported in the literature. The authors describe a remarkable case of a large lesion leading to bony destruction and spinal cord compression in the cervicothoracic junction with a large intrathoracic extension, which was considered to be a metastatic pulmonary disease but turned out to be actinomycosis.Clinical Presentation A 55-year-old man presented with acute tetraparesis. Magnetic resonance imaging (MRI) and computed tomography (CT) imaging showed vertebral body collapse of T1 and partially C7 with spinal cord compression as well as a mass in the right upper lobe with multiple intrapulmonary nodules. Moreover, dorsal elements (laminae and spinous process) were also involved and partially destructed. Differential diagnosis favored metastatic pulmonary disease.Intervention Decompression surgery was performed by anterior corpectomy of T1, stabilization with an expandable titanium cage and additional anterior plate C7–T2. Histology revealed typical sulfur granules. Microbiology exams were positive for Actinobacillus actinomycetemcomitans. There was no proof of malignancy in thoracic biopsy in the late diagnostic work-up. To prevent instrumentation failure, an external immobilization (halo fixation) was applied until complete fusion was documented in CT during the postoperative course. After an 11-month course of ampicillin/sulbactam, there was complete resolution of the intrapulmonary and spinal pathology.Conclusion Thoracic actinomycosis with spinal involvement is a rare disease. Therefore, diagnosis may be difficult. Surgical intervention, correct diagnosis, and specific long-term antibiotic treatment resulted in favorable outcome.
Keywords: actinomycosis; Actinobacillus actinomycetemcomitans; osteomyelitis; spinal; pulmonary